PENERAPAN PASAL 2 AYAT (1) JO PASAL 10 UNDANG-UNDANG RI NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG (Studi Putusan Nomor 89Pid.Sus2022PN Lsm) - Juanita, Liana (Parhesia, 2024)
PENERAPAN PASAL 2 AYAT (1) JO PASAL 10 UNDANG-UNDANG RI NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG (Studi Putusan Nomor 89/Pid.Sus/2022/PN Lsm) LIANA JUANITA D1A019322 APPLICATION OF ARTICLE 2 PARAGRAPH (1) JO ARTICLE 10 OF THE LAW OF THE RI NUMBER 21 OF 2007 CONCERNING ERADICATION OF THE CRIMINAL ACT OF TRAFFICKING IN PEOPLE (Study Decision Number 89/Pid.Sus/2022/PN Lsm) ABSTRACT The purpose of this research is to find out and analyze the judge's considerations in imposing criminal sanctions on perpetrators of criminal acts who assist or attempt to carry out human trafficking in decision Number 89/Pid.Sus/2022/PN Lsm and the application of Article 2 Paragraph (1) in conjunction with Article 10 of the Law Republic of Indonesia Number 21 of 2007 concerning Eradication of the Crime of Human Trafficking in decision Number 89/Pid.Sus/2022/PN Lsm. This research is normative legal research using the statutory, conceptual, and case approaches. The results of the study can be concluded that (1) the judge's consideration in decision Number 89/Pid.Sus/202/PN Lsm was sufficient to impose a crime on the defendant, starting from the statements of the witnesses, the defendant's statement, and the evidence presented at the trial, making it easier for judges to consider the right decision. (2) the application of the crime against the defendant is not appropriate if it refers to the Principle of Legality because the sentence imposed is below the particular minimum limit of the Law on the Eradication of Criminal Acts of Trafficking in Persons and the judge's decision does not reflect legal certainty. Keywords: human trafficking, application of the article, judge's consideration.